Artemisia biennis Willd.: Anti-Nociceptive effects and possible mechanisms of action. (25th March 2021) - Zarei, Mohammad; Ahmadimoghaddam, Davoud; Mohammadi, Saeed
Abstract: Ethnopharmacological relevance : Artemisia biennis Willd. (Dermane in Persian) has been used as an antinociceptive remedy in Iranian folkloric medicine. Objective: The aim of the present study was to evaluate the anti-nociceptive effects of Artemisia biennis Willd. aerial part essential oil (ABAEO) on male Swiss mice. Materials and methods: Nociceptive pain techniques including acetic acid-induced writhing (AAIW), formalin-induced paw licking (FPL), glutamate-induced paw licking (GPL), and tail-flick (TF) models were applied. We assessed opioid and L-arginine-NO-cGMP-KATP pathways to detect the possible anti-nociceptive properties of ABAEO. In addition, neuropathic pain was induced by the cervical spinal cord contusion model. Results: ABAEO (120 mg/kg) had a significant anti-nociceptive activities in comparison to the control animals (p < 0.05) in the AAIW, TF, GPL, and FPL assays. The selective opioid antagonist (naloxonazine) administration in the AAIW test alleviated the anti-nociceptive effect of ABAEO (p < 0.05). L-arginine, methylene blue, and glibenclamide treatment prevented the ABAEO anti-nociceptive effects (p < 0.05); however, sodium nitroprusside could profoundly potentiate the ABAEO-associated antinociception in the FPL (phase II) test (p < 0.05). In nociceptive pain models, Cr (one of the main constituents of ABAEO) showed significant anti-nociceptive effects (p < 0.05). Moreover, the von Frey results indicated that ABAEO could attenuate mechanical allodynia in mice. Conclusion: Our observation revealed the anti-nociceptive effects of ABAEO in male mice. These effects could include, at least in part, modulating glutamatergic mechanisms via opioid systems. Our data output also indicates activating the L-arginine-NO-cGMP-KATP system in ABAEO anti-nociceptive activities. Graphical abstract: Image 1